Pengaruh Kepemilikan Keluarga dan Efektivitas Dewan Komisaris terhadap nilai perusahaan yang tergabung dalam LQ 45 tahun 2012-2013 - Apri Dwi Astuti, Arinal Muna (Program Studi Akuntansi, Universitas Kuningan, 2017)
The purpose of this study was to examine and analyze family ownership and board of director effectively to the firms value. This study used 30 firms as a sample is consistently listed on LQ 45 in Indonesia Stock Exchange during 2012-2014. This research aimed to examine the effect of ownership stucture and management structure on firm value. Ownership structure was reflected by family ownership. Management structure was reflected by board of director effectively. Firm value was reflected by the stock price. The sample was determined by using purposive sampling. Analysis of data in this study used SPSS.The result showed that family had effect on firm value. Board of director effectively had effect on firm value.